IL-17-driven induction of Paneth cell antimicrobial functions protects the host from microbiota dysbiosis and inflammation in the ileum - Brabec, Tomáš; Vobořil, Matouš; Schierová, Dagmar; Valter, Evgeny; Šplíchalová, Iva; Dobeš, Jan; Březina, Jiří; Dobešová, Martina; Aidarova, Aigerim; Jakubec, Martin; Manning, Jasper; Blumberg, Richard; et al. (Mucosal immunology, 2023)
Interleukin (IL)-17 protects epithelial barriers by inducing the secretion of antimicrobial peptides. However, the effect of IL-17 on Paneth cells (PCs), the major producers of antimicrobial peptides in the small intestine, is unclear. Here, we show that the targeted ablation of the IL-17 receptor (IL-17R) in PCs disrupts their antimicrobial functions and decreases the frequency of ileal PCs. These changes become more pronounced after colonization with IL-17 inducing segmented filamentous bacteria. Mice with PCs that lack IL-17R show an increased inflammatory transcriptional profile in the ileum along with the severity of experimentally induced ileitis. These changes are associated with a decrease in the diversity of gut microbiota that induces a severe ileum pathology upon transfer to genetically susceptible mice, which can be prevented by the systemic administration of IL-17a/f in microbiota recipients. In an exploratory analysis of a small cohort of pediatric patients with Crohn's disease, we have found that a portion of these patients exhibits a low number of lysozyme-expressing ileal PCs and a high ileitis severity score, resembling the phenotype of mice with IL-17R-deficient PCs. Our study identifies IL-17R-dependent signaling in PCs as an important mechanism that maintains ileal homeostasis through the prevention of dysbiosis.
Keywords: Animals; receptory interleukinu-17; Ileum; zánět; Antimicrobial Peptides; dítě; Interleukin-17; ileum; interleukin-17; Ileitis; Receptors, Interleukin-17; lidé; Mice; Microbiota; antimikrobiální peptidy; myši; Paneth Cells; Inflammation; mikrobiota; Panethovy buňky; Dysbiosis; dysbióza; Child; ileitida; zvířata; Humans